2019
DOI: 10.4103/ipj.ipj_3_20
|View full text |Cite
|
Sign up to set email alerts
|

Association of educational stress with depression, anxiety, and substance use among medical and engineering undergraduates in India

Abstract: Background: Students pursuing higher education are subject to high stress levels which could be associated with dysfunctional coping. Maladaptive coping is known to be operative in manifesting as psychopathology as depression, anxiety, suicidal ideation, and substance abuse. This study aimed to elaborate the psychological morbidity among professional undergraduates in general and medical students in particular, its evolution over the years and its psychosocial correlates. Methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Ne' Eman-Haviv & Bonny-Noach, 2019). This is also supported by Saxena et al (2019) findings suggesting that students use psychoactive substances to cope with academic stress and associated psychopathological symptoms such as depression and anxiety. Also, studies have shown individuals use substance use to cope with social anxiety (Pant, 2023).…”
Section: Introductionsupporting
confidence: 57%
“…Ne' Eman-Haviv & Bonny-Noach, 2019). This is also supported by Saxena et al (2019) findings suggesting that students use psychoactive substances to cope with academic stress and associated psychopathological symptoms such as depression and anxiety. Also, studies have shown individuals use substance use to cope with social anxiety (Pant, 2023).…”
Section: Introductionsupporting
confidence: 57%
“…This theory explains the higher vulnerability of engineering students to deteriorated mental health across the world (Danowitz & Beddoes, 2018; Deziel et al, 2013; Negi et al, 2019; Hargis et al, 2021). In terms of the type of mental disorders, depression (Fatimah et al, 2016; Hegenauer, 2018; Naseem & Munaf, 2017; Nezam et al (2020); Saxena et al, 2019), suicidality (Banerjee & Chatterjee, 2016; Naseem & Munaf, 2017), anxiety (Balaji et al, 2019; Saxena et al, 2019), and substance use (Saxena et al, 2019) are rampant among engineering students.…”
Section: Introductionmentioning
confidence: 99%
“…Besides psychological problems such as depression, stress is also reported to play a major role in student wellbeing (15)(16)(17). Greater perceived academic stress, including increases in perceived academic workload, and higher levels of loneliness within the academic context, reveal a stronger effect on depression than do indicators of cumulative academic demands or academic grades (18).…”
Section: Introductionmentioning
confidence: 99%